2016
DOI: 10.1098/rsif.2016.0613
|View full text |Cite
|
Sign up to set email alerts
|

Physical confinement signals regulate the organization of stem cells in three dimensions

Abstract: During embryogenesis, the spherical inner cell mass (ICM) proliferates in the confined environment of a blastocyst. Embryonic stem cells (ESCs) are derived from the ICM, and mimicking embryogenesis in vitro, mouse ESCs (mESCs) are often cultured in hanging droplets. This promotes the formation of a spheroid as the cells sediment and aggregate owing to increased physical confinement and cell-cell interactions. In contrast, mESCs form two-dimensional monolayers on flat substrates and it remains unclear if the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [1,3,4,5,7,8,10,11,12,13,14,15,16,17,18,19,20]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition. Studies of cell behavior on nanocomposite surfaces are limited [1,3,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [1,3,4,5,7,8,10,11,12,13,14,15,16,17,18,19,20]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition. Studies of cell behavior on nanocomposite surfaces are limited [1,3,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used micro- and nanometer-scale engineered structures to mimic extracellular matrices and other biological structures, which have led to a groundbreaking understanding of the physical cues and molecular signal transduction pathways for integrin activated focal adhesion, protein adsorption, and pseudopodia formation [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [ 1 , 3 , 4 , 5 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition. Studies of cell behavior on nanocomposite surfaces are limited [ 1 , 3 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it is reasonable to assume that Hs68 cell–substrate, HaCaT cell–substrate, HaCaT–HaCaT, Hs68–Hs68, and Hs68–HaCaT cell interactions must be considered simultaneously . The current reports indicate that the formation of spheroids could be promoted when the cell–cell interaction overrides the effect of cell–substrate. Figures and show that both monocultured HaCaT and Hs68 cells could not spread well or were suspended on the only chitosan substrate or the blended substrates with low PCL content. It is reasonable to suggest the Hs68 cell–substrate and HaCaT cell–substrate interactions might be relatively weak.…”
Section: Discussionmentioning
confidence: 95%
“…Cell function, adhesion behavior, and morphology are often influenced by their micro-environments [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. When cells adhere to a surface, this micro-environment is highly influenced by the surface itself.…”
Section: Introductionmentioning
confidence: 99%